VCSEL-Based Optical Frequency Combs: Study of its Polarization Dynamics under Gain Switching and Polarization Selective Optical Injection Locking - Quirce, A.; de Dios, C.; Valle, A.; Prior, E.; Pesquera, L.; Panajotov, K.; Palaci, J.; Meissner, P.; Acedo, P. (Proceedings / International Conference on Transparent Optical Networks, 2018)
First, we report on a theoretical study of the polarization dynamics of a 1550 nm Vertical-Cavity Surface-Emitting Laser (VCSEL) subject to large amplitude gain switching (GS) modulation in order to get optical frequency combs (OFC). Our results show that thanks to the generation of two orthogonal linearly polarized combs the resulting overall optical frequency comb is much wider that the one of the main polarization. The theoretical dependences of the two combs on the amplitude and frequency modulation are also analysed. Our simulations are in good agreement with previous experiments already reported in the literature.Next, we study experimentally the polarization frequency comb dynamics of gain-switched VCSEL under parallel, orthogonal and combined optical injection locking (OIL). When parallel OIL is applied to the GS-VCSEL, the parallel comb is only affected at high OIL ratios and the orthogonal comb is enhanced improving the symmetry of the overall comb. For orthogonal OIL, the overall comb is narrower and dominated by the orthogonal comb as the quality of the parallel comb is quickly degraded. For a combined optical injection, the quality of the total comb in terms of span and flatness improves. Remarkably, a 10% wider frequency comb is obtained in this case. Period doubling is observed for the three types of OIL.